DEVELOPMENT OF GUIDED INQUIRY MODEL OF SCIENCE LEARNING TOOLS TO TRAIN SCIENCE PROCESS SKILLS AND IMPROVE STUDENT LEARNING OUTCOMES - Yuni Ardiyanti, Naning (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2022)
This research aimed to develop science learning materials (lesson plans, student worksheets, student book, and learning achievement test) based on the guided inquiry learning model using the 4D development model to facilitate students' science process skills and improve their learning achievement in environmental pollution. The learning materials were trialed on 35 junior high school students using a one-group pretest-posttest design, and the results were analyzed descriptively using quantitative-qualitative methods. The findings showed that: (1) the learning materials were valid (scored in the valid category of 3.00); (2) the materials were practical, with good implementation (scored in the good category of 3.8), readable worksheets and student books (students found the content and appearance interesting), and a very positive student response (85.6%); and (3) the learning materials were effective, with outstanding student activities in practicing science process skills (scored in the high category of 38.5%), very high student science process skills as shown by the achievement in the student worksheets (scored in the very high category of 3.46), and increased student learning achievement (N-Gain: 0.2-1.0). In conclusion, the science learning materials developed based on the guided inquiry learning model are eligible to facilitate students' science process skills and improve their learning achievement in junior high school.